Tips and Tricks for Performing a Successful Gonioscopy-assisted Transluminal Trabeculotomy for Beginner Ophthalmic Surgeons - Mahesh Bharathi (TNOA Journal of Ophthalmic Science and Research)
Gonioscopy-assisted transluminal trabeculotomy (GATT) is a minimally invasive glaucoma surgery (MIGS) technique that enhances aqueous outflow by disrupting the trabecular meshwork and inner wall of Schlemm’s canal. Initially described for congenital glaucoma, it has gained popularity as an effective option for primary and secondary open-angle glaucoma. This article provides a comprehensive guide for beginner ophthalmic surgeons to optimize surgical efficiency, minimise complications, and improve outcomes in GATT. Key considerations include patient selection, pre-operative assessment, and intra-operative techniques such as angle visualization, controlled Schlemm’s canal cannulation, and trabecular meshwork incision. Strategies for managing intra-operative challenges like hyphaema and canal obstruction are also discussed. Post-operative care focusses on intraocular pressure monitoring, inflammation control, and long-term success factors. With proper training and adherence to the best practices, GATT offers a safe and effective method for reducing intra-ocular pressure while preserving future surgical options.